A rapidly-banding component of animal DNA preparations that interferes with buoyant density studies - Kurnit, David M. (1974)
Rapidly-banding components of purified animal cell DNA's have been observed which have abnormal buoyant densities and show anomalous band profiles when centrifuged to equilibrium in cesium salts. These components interfere with the separation of animal DNA fractions and with the analysis of animal cell DNA's by buoyant density techniques. They can be detected by examining photographs of analytical buoyant-density ultracentrifugations before equilibrium has been reached. These rapidly-banding components are removed by phenol treatment.